Residual Strength Parameter Method for Slope stability on a Toll Road with Expansive Clay - Goji Pamungkas; Thomas Triadi Putranto; Suharyanto; Muhrozi; Yanuar Niko Priambodo (UIR PRESS, 2022)
The decreasing stability phenomenon needs to be considered during the design of cut slopes on problematic soil. Excavation slope of toll road construction tends to fail when it lies above clay-shale strata. Certain common correlations and ordinary analytical methods are not recommended for safety calculation. This study is intended to find out the characteristic of clay-shale and proper slope inclination design on Semarang Batang Toll Road. The behaviour of a clay-shale area on the cut slope of Batang-Semarang toll road segment STA 438+000–STA 439+000 was identified. The degradable and expansive properties caused slope failure of the initial design with an inclination of 1 H: 1 V. Laboratory tests found that the soil had a clay faction > 40% and can be categorized as high plasticity (LL > 50%). An empirical approach determined that the residual shear strength decreased to phi < 6 degrees. To describe the swelling after the excavation stage, the flow deformation was determined by a finite element simulation. During the swelling phase, the pore water pressure was maintained at a certain value, and a gentler slope fulfilled the minimum safety factor with an inclination of 1 V: 3 H. Furthermore, the shear strength of the clay-shale was reduced to that for a fully softened material, and all the slope factors for safety moved to a critical state. According to the simulation, the minimum suggested slope inclination is 5 H: 1 V. This approach is important for the maintenance of pore water pressure and the prevention of an additional reduction in the shear strength so as to avoid slope failure on clay-shale regions in the yielding stage.